Unveiling the Injustice Behind Employers’ Diploma Withholding Practices in Indonesia - Ranti, Gabriella; Rasji, Rasji (Jurnal Ilmu Hukum Kyadiren, 2026)
This study is motivated by the widespread practice of employers withholding employees’ diplomas as a form of job security, which raises serious concerns from both labor law and human rights perspectives in Indonesia. The purpose of this research is to assess the conformity of this practice with the principles of justice, freedom of contract, and human rights protection, as well as to analyze the legal remedies available to employees for reclaiming ownership of their diplomas through non-litigation and litigation mechanisms. The study employs a normative juridical approach, analyzing relevant laws and regulations, legal doctrines, and court decisions. The findings indicate that the withholding of diplomas violates fundamental principles of labor law and infringes upon employees’ personal property rights. The most effective means of resolution is mediation, and if such efforts fail, legal action through the Industrial Relations Court. In conclusion, this practice should be explicitly prohibited through legislative reform to ensure justice and the protection of workers’ rights.